(untitled) (Research, Society and Development, 2021)
The aim was to compare and morphologically quantify the pulmonary epithelium of hypertensive rats exposed to high intensity interval training (HIIT). This is an experimental study, in which male Wistar Kyoto rats of the spontaneously hypertensive strain (SHR) (n = 16) were divided into Group 01 (Spontaneously hypertensive sedentary controls (SHR, n = 8)) and Group 02 (Spontaneously trained hypertensive patients (SHR + T, n = 8)). The exercise was performed on a mat adapted for rodents, for 50 minutes / day, 5 days / week for a total of 8 weeks. The intervals between running shots were 3 minutes with 60% of the exhaustion speed. After 8 weeks of training, the rats were euthanized and performed an autopsy to remove the lungs. The tissues, after making the slides, were stained with Hematoxylin and Eosin (HE) to assess the inflammatory infiltrate by quantifying the peribronchial region using a semi-quantitative method. A significant reduction in the weight of SHR + T rats was observed when compared to SHR without intervention. In the morphometric comparison between the areas of the airway, pulmonary artery, pulmonary artery lumen and the alveolar area, no statistically significant differences were observed. Through this study it was possible to prove the effectiveness of HIIT training in physical conditioning, weight loss and with a positive impact on the control of arterial hypertension, however in relation to the improvement of the lung parenchyma observed a difference in the results. We think that a longer period of exercise is necessary for there to be such a change in epithelial and parenchymal changes.